Hearing status in patients with rheumatoid arthritis - Keyvan Kiakojuri; Behnaz Yousef-Ghahari; Sanaz Soltanparast; Mohsen Monadi (Babol University of Medical Sciences, 2019)
Background: Previous studies showed that one of the complications of rheumatoid arthritis disease was auditory disorder. The goal of the present study was to compare the auditory status in patients with rheumatoid arthritis and healthy individuals. Methods: In the present case-control study, 30 normal persons and 60 persons with rheumatoid arthritis with mean age of 46.72 and standard deviation of 6.76 of both genders were appraised using pure tone audiometry, tympanometry and speech audiometry. The mean disease duration in patients with rheumatoid arthritis was 12.51±6.09 years. Results: The frequency of hearing loss in rheumatoid arthritis group was significantly more than the control group (p=0.001). All patients had sensorineural hearing loss. Only in 5% of rheumatoid arthritis group, abnormal tympanometry (as type) was reported. Speech discrimination score analysis showed significant difference between the patients with rheumatoid arthritis and controls. In terms of hearing threshold level, the mean hearing threshold level (in 2000, 4000 and 8000 Hz frequencies) of the patients with rheumatoid arthritis was significantly higher than control group in both ears (p<0.05). A positive significant correlation was found among mean hearing threshold level in 4000 and 8000 Hz frequencies and rheumatoid arthritis duration in both ears. Conclusion: The frequency of hearing loss and the average hearing threshold in RA patients were higher than healthy individuals. The most common type hearing loss is sensorineural.